Presepsi Masyarakat Tengger tentang Kemanfaatan Etnobotani sebagai Obat Herbal - Yuli Hariyati; Sigit Soeparjono; Setiyono Setiyono; Priyo Sugeng Winarto (Jurnal Ilmu Pertanian Indonesia, 2020)
The synthesis of various local wisdom values in the Tengger society in terms of utilization of ethnobotany resources as herbal products for health has long been existed in the scope of the Tengger locality and surrounding areas. The comparative advantage of Tengger ethnobotany certainly has potential that can be developed through certain strategies in order to be able to further contribute to the operationalization of the research, development, and application of science and technology (RISBANGRAPIPTEK) in the Field of Health and Medicine 2005–2025 towards a state of adequacy of raw materials and preparations of standardized herbal medicinal products and Indonesia branded for the Indonesian people. Therefore, the research question raised is the formulation of a strategy that must be immediately created and can be used as a reference for the activities of Tenggerese etnobotanical resource development to become a superior branded Indonesian biotechnology commercial product. The sampling method in this study was done by purposive sampling. The method of data collection was done by observation, interviews which included primary data and literature studies which were secondary data. The research method used was descriptive and analytic. The results showed that: 1) the perception map of the Tengger Society towards medicinal plants was classified as a moderate and the relationship of the characteristics of the Tengger Society did not have a close correlation to herbal medicines with a value of r less than 0.8. 2) Determinants that influence the influence of society on traditional medicine are age (X1), income (X3), and education (X4), while number of family dependents (X2) not significant effect. Keywords: determinant factors, ethnobotany, perception